Preliminary evaluation of the effectiveness of autologous bone marrow stem cell therapy in supporting the treatment of biliary atresia - Hoa, Nguyen Pham Anh; Khang, Hoang Tuan; Hien, Pham Duy; Binh, Nguyen Thanh; Ha, Dang Thi; Na, Bach Thi Ly; Yen, Pham Thi Hai; Tam, Tran Duc; Long, Phan Hong; Hoan, Vu Manh; Hanh, Nguyen Duc; Thanh, Nguyen Duc; et al. (Tạp chí Nghiên cứu Y học, 2025)
Biliary atresia (BA) is a rare hepatobiliary disorder. Stem cell therapy is expected to serve as a supportive treatment to slow fibrosis progression. This study aimed to assess the therapeutic efficacy and the safety of the Kasai procedure combined with autologous bone marrow stem cell (ABMSC) infusion. From May 2021 to December 2024, 82 pediatric BA patientswho underwent the combined treatment at Vietnam National Children’s Hospital were enrolled. The mean age at surgery was 76.8 ± 12.6 days. No severe complication occurred during stem cell harvesting or follow-up time frame. The successful bile drainage rate at 6 months post-surgery was 58.5%. Post-operatively, transaminase levels gradually declined and stabilized from 12 months. GGT levels peaked at 3 months (p < 0.001), then declined from 6 months and stayed stabilized. PELD scores improved significantly. Liver tissue elasticity increased gradually until 12 months (14.6 ± 4.5kPa) and then stabilized. Mean post-surgical survival was 34.3 ± 1.7 months, and 30-month survival rate was 64.7%. Portal hypertension occurred in 55% of patients, mostly in those with high-dose MSC therapy. Despite benefits achieved in liver function improvement, progressive cirrhosis remains a challenge, necessitating further research on optimizing stem cell therapy in BA treatment.